Sustainable nanocellulose reinforced polyethersulfone membranes coated with tetraethyl orthosilicate for separation of phosphoric acid from wastewater - Nora Yehia Selem; El-Shimaa M. El-Zahed; Heba Abdallah; Samah A. Hawash (Applied Water Science)
Abstract Extraction of cellulose nanocrystal (CNC) from agricultural waste is a cost-effective and environmentally beneficial technique. Six nanocomposite membranes were created by combining varying concentrations of CNC and tetraethyl orthosilicate (TEOS) with polyethersulfone (PES) for the higher removal efficiency of phosphoric acid from wastewater. It was found that the M6 (CNCs/PES/TEOS) membrane has a higher separation efficiency of 82.4% and an appropriate water flux of 169.2 (L.mole/h) at a phosphoric acid concentration of 50 ppm. This result indicated that using 1 wt. % CNCs and 1 wt. % TEOS in the polymer mixture enhances the polymeric membrane's mechanical properties and hydrophilic characteristics with a moderate porosity close to 42%. The mechanical test revealed that the M6 membrane, with a strength of 30.8 MPa and an elongation of 45.17%, exhibited good compressible behavior and flexibility. Moreover, it has an optimal antifouling capability, with a flux recovery percentage close to 99%.